Good practice guidance on health impact assessment. (International Council on Mining & Metals, 2010)
This manual is intended as a practical tool to assist companies in protecting the health and wellbeing of their workforce and local communities. It sets out an overview of how mining and metals operations can affect the health and wellbeing of local communities, describes typical health impact assessment processes and outlines a methodology for undertaking a rapid assessment so that in-house practitioners are involved from the start. This publication recognizes the imperative to integrate health impact assessment with environmental and social impact assessments and provides the reader with management tools to achieve this.